2005
DOI: 10.1007/s00109-005-0689-6
|View full text |Cite|
|
Sign up to set email alerts
|

T-cell-based vaccination for morphological and functional neuroprotection in a rat model of chronically elevated intraocular pressure

Abstract: Acute or chronic glaucoma is often associated with an increase in intraocular pressure (IOP). In many patients, however, therapeutic pressure reduction does not halt disease progression. Neuroprotection has been proposed as a complementary therapeutic approach. We previously demonstrated effective T-cell-based neuroprotection in experimental animals vaccinated with the synthetic copolymer glatiramer acetate (copolymer-1, Cop-1), a weak agonist of self-antigens. This study was undertaken to test different route… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 59 publications
3
54
0
Order By: Relevance
“…Therefore, the identification of other microglia-released factors involved in neuroprotection will likely contribute to explaining why other types of neurotoxicity (a shift of CGNs to nondepolarizing con-ditions or excitotoxicity) are significantly reverted by MCM, but not by exogenous SOD1. Differences in SOD1 neuroprotection against different toxic stimuli are in line with previous works that have or have not found neuroprotective effects of SOD1 in nonconditioned media, sometimes using very high amounts of exogenously added protein [60,61,62,63,64,65,66]. To further complicate this situation, it has to be considered that SOD1 may act on target cells both through its catalytic activity and through receptor interaction [46,47].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Therefore, the identification of other microglia-released factors involved in neuroprotection will likely contribute to explaining why other types of neurotoxicity (a shift of CGNs to nondepolarizing con-ditions or excitotoxicity) are significantly reverted by MCM, but not by exogenous SOD1. Differences in SOD1 neuroprotection against different toxic stimuli are in line with previous works that have or have not found neuroprotective effects of SOD1 in nonconditioned media, sometimes using very high amounts of exogenously added protein [60,61,62,63,64,65,66]. To further complicate this situation, it has to be considered that SOD1 may act on target cells both through its catalytic activity and through receptor interaction [46,47].…”
Section: Discussionmentioning
confidence: 69%
“…While superoxide dismutase is usually released by cells in its SOD3 isoform [58,59], also SOD1 is released by several cell lines [31,32,33,34]. Moreover, high concentrations of SOD1 may protect neurons from some toxic insults [60,61,62,63,64,65,66]. Here we show that SOD1 is produced and released by microglia and is a neuroprotective factor against 6-OHDA neurotoxicity in CGNs.…”
Section: Discussionmentioning
confidence: 82%
“…A single injection of GA is protective in acute models of CNS insults (13,15), whereas in chronic models occasional boosting rather than daily is required for a long-lasting protective effect (14). In a model of chronically elevated intraocular pressure, for example, weekly administration of adjuvant-free GA was found to result in neuroprotection (19). The neuroprotective effect of GA has been attributed in part to production of brainderived neurotrophic factor (26).…”
Section: Discussionmentioning
confidence: 99%
“…The GA was repeatedly injected without adjuvant and according to a regimen similar to that used to evoke neuroprotection in a model of chronic elevation of intraocular pressure (19); a daily injection was ineffective in this model.…”
Section: Il-4mentioning
confidence: 99%
“…They found that vaccination with this agent can protect RGCs from the consequences of elevated IOP in rats. 90 Therefore, T-cell-mediated responses may participate in glaucomaassociated optic neuropathy. On the basis of the use of DNA microarrays, Mao et al 91 had previously looked for genes specifically involved in human T-cell activation, and one of them was WDR36, which highly co-regulated with interleukin-2.…”
Section: Wdr36 At the Glc1g Locusmentioning
confidence: 99%